Tinjuan Pustaka: Analisis Ergonomi Posisi Berkendara pada Rangka Chopper Berdasarkan Antropometri Pengendara - Gaza Juliyanto; Dan Mugisidi (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
Ergonomic analysis of riding posture on a chopper frame based on rider anthropometry is crucial to ensure comfort and safety during riding. This study examines the suitability of the chopper frame's dimensions with the rider's body size using representative anthropometric data. Through measurement and comparison methods, the research identifies geometric mismatches in seating position and control placement that can cause discomfort, muscle fatigue, and long-term injury risks. The analysis results indicate that seat dimensions and frame height need adjustment to match the rider’s anthropometric percentiles to optimize an ergonomic riding posture. This research offers ergonomic design recommendations for chopper frames to enhance comfort and reduce injury risks, using anthropometry as a design reference for two-wheeled vehicles. The findings are expected to guide the development of safer and more comfortable chopper motorcycles, supporting national ergonomic standards